2013
DOI: 10.1021/ac402383n
|View full text |Cite
|
Sign up to set email alerts
|

Self-Digitization of Samples into a High-Density Microfluidic Bottom-Well Array

Abstract: This paper describes a sample digitization method that generates tens of thousands of nanoliter-sized droplets in a high-density array in a matter of minutes. We show that the sample digitization depends on both the geometric design of the microfluidic device and the viscoelastic forces between the aqueous sample and a continuous oil phase. Our design avoids sample loss: Samples are split into tens of thousands of discreet volumes with close to 100% efficiency without the need for any expensive valving or pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Performing these analyses in individually addressable volumes may also allow for further downstream analysis(Fig 4A). 27 As an alternative to high droplet capacity devices, Kreutz el al. showed that a wide dynamic range and high copy number resolution can be achieved by using a smaller number of chambers and multivolume digital PCR (Fig 4B).…”
Section: Microfluidics As a Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing these analyses in individually addressable volumes may also allow for further downstream analysis(Fig 4A). 27 As an alternative to high droplet capacity devices, Kreutz el al. showed that a wide dynamic range and high copy number resolution can be achieved by using a smaller number of chambers and multivolume digital PCR (Fig 4B).…”
Section: Microfluidics As a Solutionmentioning
confidence: 99%
“…[Reprinted (adapted) with permission from ref. 27.Copyright 2013 American Chemical Society]. Signal accumulation allows for the counting of positive reactions.…”
Section: Figmentioning
confidence: 99%
“…Several spontaneous fluid compartmentalization methods have been reported for dPCR, including vacuum packaging, 31 dissolution of pre-coated monosaccharides, 32 or passive two-phase flow manipulation by microfluidic geometry. 29 Compared to these methods, our approach affords several advantages: first, no special geometrical design of microstructures and deliberate control of two-phase fluid system are required; second, it eases device fabrication and assay operation; third, it avoids the possible sample evaporation under vacuum or introduction of contaminants along with the coating materials; lastly, it is applicable to different polymer materials than PDMS as it does not rely on the gas permeability of PDMS. Therefore the μSAAC is amenable to the well-established polymer chip manufacturing to further reduce the chip cost.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, various microwell-based devices have been reported to achieve equipment-free or spontaneous fluid compartmentalization driven by different mechanisms, including the self-priming chip using vacuum packaging, 31 the monosaccharide pre-coated microwell chip for dissolution-guided wetting, 32 and the self-digitization chips based on passive two-phase flow manipulation by microfluidic geometry. 29 Paper-based devices, such as provide a suitable platform for convenient fluid transport and manipulation based on spontaneous wetting. 33, 34 For instance, a SlipPAD device has been developed to synergistically marry the ability of the SlipChip for high-throughput, multiplexed sensing with the advantages of the paper-based chips in simple fabrication and spontaneous fluid transport.…”
Section: Introductionmentioning
confidence: 99%
“…First, the introduction of an immiscible phase takes advantage of an existing robust technology, self-digitization (SD) chip, we developed. [19] This technology employs inherent fluidic phenomena to spontaneously divide an aqueous solution into nanoliter-scale water-in-oil plugs in an array of microfluidic chambers. Each water-in-oil emulsion plug formed on the SD-DEP chip can function as an independent chemical reactor, handling an extremely small volume of liquid containing cells and reagents for following molecular analysis of single cell lysates.…”
mentioning
confidence: 99%